Welcome to Scribd, the world's digital library. Read, publish, and share books and documents. See more ➡
Standard view
Full view
of .
×
0 of .
Results for:
P. 1
Mathematical Methods For Physicists Webber and Arfken Selected Solutions ch. 5

# Mathematical Methods For Physicists Webber and Arfken Selected Solutions ch. 5

Ratings: 0|Views: 881|Likes:
Ch. 5: 5.4.1, 5.4.2, 5.4.3, 5.5.2, 5.5.4
Ch. 5: 5.4.1, 5.4.2, 5.4.3, 5.5.2, 5.5.4

### Availability:

See More
See less

04/25/2013

pdf

text

original

Physics 451 Fall 2004Homework Assignment #7 — Solutions
Textbook problems: Ch. 5: 5.4.1, 5.4.2, 5.4.3, 5.5.2, 5.5.4Chapter 55.4.1 Given the seriesln(1 +
x
) =
x
x
2
2+
x
3
3
x
4
4+
···
,
1
< x
1show thatln
1 +
x
1
x
= 2
x
+
x
3
3+
x
5
5+
···
,
1
< x <
1We use the property ln(
a/b
) = ln
a
ln
b
to writeln
1 +
x
1
x
= ln(1 +
x
)
ln(1
x
) =
n
=1
(
1)
n
+1
x
n
n
n
=1
(
1)
n
+1
(
x
)
n
n
=
n
=1
((
1)
n
+1
+ 1)
x
n
n
= 2
n
odd
x
n
n
Note that, since we use the ln(1 +
x
) series for both +
x
and
x
, the commonrange of convergence is the intersection of
1
< x
1 and
1
<
x
1, namely
|
x
|
<
1.5.4.2 Determine the values of the coeﬃcients
a
1
,
a
2
, and
a
3
that will make (1+
a
1
x
+
a
2
x
2
+
a
3
x
3
)ln(1 +
x
) converge as
n
4
. Find the resulting series.Using the expansion for ln(1 +
x
), we write(1 +
a
1
x
+
a
2
x
2
+
a
3
x
3
)ln(1 +
x
)=
n
=1
(
1)
n
+1
x
n
n
+
a
1
x
n
+1
n
+
a
2
x
n
+2
n
+
a
3
x
n
+3
n
We want to collect identical powers of
x
on the right hand side. To do this, wemust shift the index
n
according to
n
n
1,
n
n
2 and
n
n
3 forthe second, third and last terms on the right hand side, respectively. After doing

so, we may combine terms with powers
x
4
and higher. The ﬁrst few terms (
x
,
x
2
and
x
3
) may be treated as exceptions. The result is(1 +
a
1
x
+
a
2
x
2
+
a
3
x
3
)ln(1 +
x
)= (
x
12
x
2
+
13
x
3
) +
a
1
(
x
2
12
x
3
) +
a
2
x
3
+
n
=4
(
1)
n
+1
x
n
n
a
1
x
n
n
1+
a
2
x
n
n
2
a
3
x
n
n
3
=
x
+ (
a
1
12
)
x
2
+ (
a
2
12
a
1
+
13
)
x
3
+
n
=4
(
1)
n
+1
1
n
a
1
n
1+
a
2
n
2
a
3
n
3
x
n
(1)Combining the terms over a common denominator yields
1
n
a
1
n
1+
a
2
n
2
a
3
n
3
=(
n
1)(
n
2)(
n
3)
a
1
n
(
n
2)(
n
3) +
a
2
n
(
n
1)(
n
3)
a
3
n
(
n
1)(
n
2)
n
(
n
1)(
n
2)(
n
3)=(1
a
1
+
a
2
a
3
)
n
3
+ (
6 + 5
a
1
4
a
2
+ 3
a
3
)
n
2
+(11
6
a
1
+ 3
a
2
2
a
3
)
n
6
n
(
n
1)(
n
2)(
n
3)To make this converge as
n
4
, we need to cancel the coeﬃcients of
n
3
,
n
2
and
n
in the numerator. Solving for1
a
1
+
a
2
a
3
= 0
,
6+5
a
1
4
a
2
+3
a
3
= 0
,
11
6
a
1
+3
a
2
2
a
3
= 0yields the solution
a
1
= 3
, a
2
= 3
, a
3
= 1Finally, inserting this back into (1), we obtain(1+3
x
+3
x
2
+
x
3
)ln(1+
x
) =
x
+
52
x
2
+
116
x
3
+6
n
=4
(
1)
n
x
n
n
(
n
1)(
n
2)(
n
3)orln(1 +
x
) =
x
+
52
x
2
+
116
x
3
+ 6
n
=4
(
1)
nx
n
n
(
n
1)(
n
2)(
n
3)
(1 +
x
)
3

5.4.3 Show that
a
)
n
=2
[
ζ
(
n
)
1] = 1Using the sum formula for the Riemann zeta function, we have
n
=2
[
ζ
(
n
)
1] =
n
=2

p
=1
1
p
n
1
=
n
=2
p
=2
1
p
n
=
p
=2
n
=2
1
p
n
where in the last step we have rearranged the order of summation. In doing so,we have now changed this to a geometric series, with sum
n
=2
p
n
=
p
2
1
p
1
=1
p
(
p
1)In this case
n
=2
[
ζ
(
n
)
1] =
p
=2
1
p
(
p
1)=
p
=2
1
p
1
1
p
= 1since this is a telescoping series.
b
)
n
=2
(
1)
n
[
ζ
(
n
)
1] =12The solution to this is similar to that of part
a
1)
n
yields
n
=2
(
1)
n
[
ζ
(
n
)
1] =
n
=2
(
1)
n
p
=2
1
p
n
=
n
=2
p
=2
1(
p
)
n
=
p
=2
n
=2
1(
p
)
n
The sum over
n
is still a geometric series, this time with
n
=2
(
p
)
n
=(
p
)
2
1
(
p
)
1
=1
p
(
p
+ 1)In this case
n
=2
(
1)
n
[
ζ
(
n
)
1] =
p
=2
1
p
(
p
+ 1)=
p
=2
1
p
1
p
+ 1
=12

## Activity (3)

### Showing

AllMost RecentReviewsAll NotesLikes